Entrepreneurial self-efficacy dimensions and higher education institution performance - Bakar, Muhammad Shukri; Ramli, Azahari; Ibrahim, Najafi Auwalu; Muhammad, Ibrahim Garba (Universiti Utara Malaysia, 2017)
A detailed literature review provided consistent justification for the effect of entrepreneurial self-efficacy (ESE) on entrepreneurial intention. Recently,the literature yielded similar relationship on the link between ESE to firm performance.Although there are a significant number of studies on this effect that was mostly conducted in the private sector, they mainly focused on the composite ESE construct. The present study replicated and validated these findings with data from the public sector, specifically, higher education institutions (HEIs).Moreover, the study focused on the individual effect of all dimensions of ESE identified by Chen, Greene, and Crick (1998). Using PLS-SEM and non-probability sampling, the data were collected from 180 academic leaders from selected HEIs in Kano, Nigeria.The findings indicated that three dimensions of ESE (financial control ESE, innovation ESE, and risk taking ESE) were found to be significantly related to HEI performance, while two (management ESE and marketing ESE) were insignificantly related to HEI performance.The practical implication and suggestion for future study are also discussed.